Penetapan Tarif Parkir di Pasar Sangkumpal Bonang ditinjau dari Prinsip-Prinsip Hukum Ekonomi Syariah - Siregar, Liska Agustina; Hasibuan, Putra Halomoan; Kurniawan, Puji (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The problem in this study is the discrepancy in setting parking rates at the Sangkumpal Bonang market, Padangsidimpuan City in terms of Islamic Economic Law. This type of research is field research using a qualitative approach, the primary data source in this study is the Padangsidimpuan City Transportation Service, parking attendants and parking service users at the Sangkumpal Bonang Market. Secondary data sources were taken in the form of books, journals and documentation related to this research. The data collection techniques carried out by researchers are observation, interviews and documentation. The data analysis technique used by the researcher is descriptive data analysis. The results of the study show that the lack of effectiveness in setting parking rates in Padangsidimpuan City Regional Regulation No. 04 of 2010 and Mayor Regulation No. 32 of 2018. There is a discrepancy between the parking rates set out in the regulations and the rates applied by parking attendants in the field, causing dissatisfaction with the public and related parties regarding the rates charged. In the context of the principles of Sharia Economic Law, the determination of parking rates at the Sangkumpal Bonang market is based on the principles of fairness, balance, public benefit, trustworthiness, and transparency.